1980
DOI: 10.1093/schbul/6.1.64
|View full text |Cite
|
Sign up to set email alerts
|

A Reevaluation of Milieu Therapy for Nonchronic Schizophrenic Patients

Abstract: Until recently almost all the controlled research on milieu therapy for schizophrenic patients involved nonintensive milieus and chronic patients. Under these circumstances the effectiveness of milieus was not evident. Recent studies have suggested that intensive milieus significantly benefit nonchronic patients. These studies have indicated the importance of defining what ingredients can make a milieu therapeutic. The existing research evidence is surveyed, and the nature of what some of these ingredients mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Hospital settings were the subject of much concern and study during the 1960s and early 1970s (Gunderson, 1980). The characteristics of various hospital milieu which appear to facilitate patient recovery may give us a lead as to the direction we should follow.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital settings were the subject of much concern and study during the 1960s and early 1970s (Gunderson, 1980). The characteristics of various hospital milieu which appear to facilitate patient recovery may give us a lead as to the direction we should follow.…”
Section: Discussionmentioning
confidence: 99%
“…More supportive environments also characterized milieu therapy in this period ( 10), and today specific out‐patient facilities are designed on the basis of present knowledge of the needs for severely mentally ill. Thus, recent studies on treatment environments has investigated more specialized out‐patient or residential settings providing long‐term treatment and rehabilitation in community mental health centres, day‐programmes, group homes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Given dropout rates in trials of dynamic psychotherapies for psychosis decades ago (Gunderson, 1980), any potentially long-term treatment has lived under the shadow of questions about its acceptability and feasibility. To date, two randomized controlled trials of 6 and 8 months of MERIT, respectively, have demonstrated that between two-third and three-fifth of patients randomized to receive MERIT completed treatment (de Jong, van Donkersgoed, Timmerman, et al, 2018; Vohs et al, 2018).…”
Section: Evidence Supporting Meritmentioning
confidence: 99%